Peer pressure, academic and social experience of secondary school teenagers in the outskirts of Mbarara municipality, Uganda - Rukundo, Aloysius (Journal of Educational Sciences and Psychology, 2012)
The present study was conducted to get scientific explanation of how teenagers constructively and destructively influence others in academic and social context. Cross-sectional design, qualitative method, and focus group discussions were employed. Randomly selected students (n =40) from purposively selected secondary schools (N=4) were recruited into the study. Participants in each school were divided into groups and each group given topics of discussion. It was realized that peer pressure almost weighs equally on both positive and negative scales of teenagers’ academic and social experiences. Teenagers also had varied strategies of avoiding negative peer pressure influences. It was concluded that though teenagers knew how to bolster bad peer pressure, some find it a challenge to cut a rational balance between accepting peer engagement and being themselves.
Keywords: Peer pressure; Teenagers; Academic experiences; Social experiences; Secondary schools